2017
DOI: 10.1016/j.meatsci.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between marbling measures across principal muscles

Abstract: As marbling is a principal input into many grading systems it is important to have an accurate and reliable measurement procedure. This paper compares three approaches to measuring marbling: trained personnel, near infrared spectroscopy (NIR) and image analysis. One 25mm slice of meat was utilised from up to 12 cuts from 48 carcasses processed in Poland and France. Each slice was frozen to enable a consistent post-slaughter period then thawed for image analysis. The images were appraised by experienced beef gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
5
19
1
1
Order By: Relevance
“…While the correlations between carcass measures and carcass age were obvious and already well known [ 23 , 24 ], it was of our interest to determine the strength of any relationship between primary carcass fat and marbling measures. These results are in agreement with [ 25 ] and [ 6 ] studies, which raised questions about the ability of EUROP carcass measures to accurately predict marbling and fat composition of cuts.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…While the correlations between carcass measures and carcass age were obvious and already well known [ 23 , 24 ], it was of our interest to determine the strength of any relationship between primary carcass fat and marbling measures. These results are in agreement with [ 25 ] and [ 6 ] studies, which raised questions about the ability of EUROP carcass measures to accurately predict marbling and fat composition of cuts.…”
Section: Resultssupporting
confidence: 90%
“…Others major existing grading systems, such as the American, Australian, and Japanese one, consider marbling or intramuscular fat (IMF) content as one of the main factor to assess beef meat quality [ 5 ]. In both United States Department of Agriculture (USDA) and Australian Meat Standards (MSA) systems, marbling is evaluated on a single cross-section of the Longissimus thoracis et lumborum (LTL) muscle, which would provide a whole carcass estimate [ 6 ]. According to the USDA system, degree of marbling is the primary determination of meat carcass grade, and each grade of marbling is divided into 100 subunits [ 7 , 8 ], from “abundant” to a “practically devoid” grade.…”
Section: Introductionmentioning
confidence: 99%
“…showed some effects on the palatability and consumer's acceptability for beef (Konarska et al, 2017;Lee et al, 2018). According to studies on consumer's feedbacks, within a same marbling degree, the consumers do not prefer beef cuts with high amount of coarse marbling flecks (Lee et al, 2019;Motoyama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the degree of marbling is correlated positively to eating quality especially tenderness, juiciness, flavor and overall acceptability of beef ( Corbin et al, 2015 ; Van Ba et al, 2017 ). However, recent studies have revealed that morphological characteristics of marbling flecks (e.g., coarse and fine flecks) showed some effects on the palatability and consumer’s acceptability for beef ( Konarska et al, 2017 ; Lee et al, 2018 ). According to studies on consumer’s feedbacks, within a same marbling degree, the consumers do not prefer beef cuts with high amount of coarse marbling flecks ( Lee et al, 2019 ; Motoyama et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers tend to believe that heavily-marbled beef is more palatable than lightly-marbled beef (Hunt et al, 2014; Lee et al, 2018b; Motoyama et al, 2016). In addition, various characteristics of marbling fleck, as measured by computer image analysis, are also associated with the palatability of cooked beef (Konarska et al, 2017). A previous study reported that highly-marbled steaks with coarser marbling flecks exhibited a lower score of overall acceptability, although were more tender compared to highly-marbled steaks with evenly-distributed marbling flecks.…”
Section: Introductionmentioning
confidence: 99%